Arabidopsis flowering induced by photoperiod under 3-D clinostat rotational simulated microgravity. (January 2020) - Xie, Junyan; Zheng, Huiqiong
Abstract: The transition from vegetative growth to flowering is very important for the plant reproductive success. This process is delayed under microgravity conditions in space, but whether microgravity affects plant flowering at the molecular level is still unknown. Here, we studied the effects of altered gravity on photoperiod-controlled flowering induction by using a random positioning machine (RPM, 3-D clinostat). First, using transgenic plant pro FT : GFP in the Col-0 background and examining the expression of key genes in the photoperiod pathway, such as FT, CONSTANS ( CO ) and GIGANTEA ( GI ), we found that 3-D clinostat rotation affected the activity of the FLOWERING LOCUS T ( FT ) promoter under long-day conditions. Second, using a pro SUC2 : FT CDS: GFP construct in the ft-10 mutant background, we observed that the transport of FT from the leaves to the shoot apical meristem was also delayed by simulated microgravity under 3-D clinostation conditions compared with the 1 g stationary control. These results indicate that photoperiod-controlled plant flowering is delayed by 3-D clinostat rotation. Highlights: Down-regulation of FT in leaves by the clinorotation resulted in late flowering. Expression of FT, CO and GI was altered by the clinorotation. FT protein transferred from leaves to shoot apex was affected by the clinorotation.